2021
DOI: 10.1038/s41598-021-95419-3
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography findings in knee osteoarthritis: a prospective observational cross-sectional study of 100 patients

Abstract: Worldwide, knee osteoarthritis (KOA) accounts for 2.2% of total years lived with disability. There is a low correlation between joint tissue damage and pain intensity. Periarticular structures may be involved and cannot be identified in X-rays. To describe the main ultrasonography (USG) changes in symptomatic patients with primary KOA; to correlate the number of USG findings with KOA severity assessed by Kellgren and Lawrence (K&L) radiological scores, with pain intensity measured by a visual analogue scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…On the other hand, ultrasonography is classically recommended to assess joint effusion osteophytes, narrowing of joint space and other features ( 45 ). Besides joint effusion, we have also demonstrated a significant percentage of knee OA patients with pes anserine bursitis, patellar tendinitis and popliteal cysts ( 28 ). Our study identified USG changes in 78% of the examined knees.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…On the other hand, ultrasonography is classically recommended to assess joint effusion osteophytes, narrowing of joint space and other features ( 45 ). Besides joint effusion, we have also demonstrated a significant percentage of knee OA patients with pes anserine bursitis, patellar tendinitis and popliteal cysts ( 28 ). Our study identified USG changes in 78% of the examined knees.…”
Section: Discussionmentioning
confidence: 84%
“…Main USG findings were small to moderate joint effusion, pes anserinus bursitis, quadriceps enthesopathy, popliteal cyst, iliotibial band tendonitis and patellar tendinitis. Together with the high prevalence of USG findings, we identified a significant positive correlation between the number of USG findings and pain intensity scores measured by a VAS (28). These periarticular changes are also sources of knee pain and target for interventions including radial shockwave therapies (46)(47)(48)(49)(50).…”
Section: Outcomes (N = 96) Baseline Mean (±Sd) After Treatment Mean (...mentioning
confidence: 81%
See 1 more Smart Citation
“…For specific ultrasonographic findings, the incidence of suprapatellar recess effusion was 55.26% and significantly higher than in control group (0.00%). Although ultrasonographic findings, including suprapatellar effusion, popliteal cyst, pes anserinus bursitis, suprapatellar tendinitis, were shown to be significantly correlated with pain intensity in knee osteoarthritis patients [25], no relationship between symptom and knee effusion alone was reported. Additional analysis of our data was done among player groups, which showed no difference of IKDC-SKF score between ultrasonographic effusion positive and negative knees of players (77.82 vs 76.56, P=0.77, unpaired t-test).…”
Section: Discussionmentioning
confidence: 87%
“…Since then more research has been conducted on tools more accurately depicting early cartilage and soft tissue damage as MRI and US. Since MRI is an expensive tool, and not readily available in any clinical setting, more effort was invested with US and its capability in defining those early soft tissue changes in KOA especially the ones related to pain and eventually leading to loss of function as concluded by Abicalaf et al [31]. Recently ultrasound has become popular among rheumatologists as the first-choice imaging for the evaluation and monitoring of KOA.…”
Section: Discussionmentioning
confidence: 99%